Discrete element method (DEM) simulation and validation of a screw feeder system - Kretz, Dominik; Hesser, Jürgen (Powder technology, 2016)
A computational particle flow simulation of a feeder which transports bulk material through a horizontal cylinder by a turning screw is presented. The objective is hereby the simulation-assisted support of system design. Such systems are used in industry to either create packages of material which have a very accurately determined mass or to produce a continuous flow of the used bulk material. The well known and common problems in practical applications are the missing stability of material flux over time, throughput changes with product quality drifts and a lack in design know how based on theoretical solutions. Therefore a simulation tool is realized by Blender software (v 2.68) to foster straight forward and goal oriented screw and apparatus design. The geometrical and physical properties of the system are adjusted to a real feeder system on which the experimental measurements are performed. Simulation parameters like wall friction, internal shear forces and angle of repose are fitted to the real experimental data. Absolute deviations are smaller than 8%. We demonstrate that a simplified particle simulation tool is able to predict properties of a real machine that progresses bulk material with different types of screws. The mass flow rate in simulation differs from the experimental mass flow rate less than 10% for different screw types and angular velocities of the screw. Qualitative properties like the inflow and outflow behavior of the bulk are compared and the conformity is verified. It is shown that quite a simple particle simulation tool is able to verify and predict properties of a machine that progresses bulk material with different types of screws. The simulation tool allows the modeling of all relevant machine parts without expensive real manufacturing and to test their characteristics.
Gesehen am 18.10.2019
Available online 8 October 2015